Application of micro-or small-scale biomass-derived fuel system for power generation - Chowdhury, S. (Springer International Publishing, 2015)
Biomass being world's largest renewable fuel source is now considered as the best alternate for fossil fuels owing to the CO 2 saving nature as well as more economical as compared to fossil fuels. Although, some pretreatment process is required in order to utilize the raw biomass for power generation. There are various systems to generate power but combined heat and power (CHP) generation has proved to be the most beneficial method to generate electricity as well as heat by recovering the surplus heat to make an overall efficiency of up to 90 . Various types of CHP systems have been discussed and compared for their working and efficiency along with their applications in different dwellings depending upon their power capacities. Moreover, biomass CHP systems have been thoroughly overviewed for their economic, energy, and environmental aspects. Â© Springer International Publishing Switzerland 2014.